HUBUNGAN POWER OTOT TUNGKAI DENGAN KEMAMPUAN LOMPAT JAUH - Saidun Saidun; Wolter Mongsidi; Muhammad Zaenal Arwih (JOKER (Jurnal Ilmu Keolahragaan), 2020)
The purpose of this study was to determine how much the relationship between leg muscle power and the long jump ability of SMPN 17 Masaloka Raya Bombana students .              The population in this study were all students of SMPN 17 Masaloka Raya Bombana , totaling 365 people . The sampling technique is done using a purposive random sampling technique which is obtained by the number of 175 people. After that, to simplify the research carried out randomly so as to get 35 people. The instrument used to measure leg muscle power is the vertical jump test and for the longjump results the long jump test is 3 attempts.              The research data were analyzed using statistical product technique techniques with a significant level of 0, 05. The results of this study indicate that there is a significant relationship between leg muscle power and the results of long jumps on SMPN 17 Masaloka Raya Bombana students. r xy = 0, 90> r tab (0.05: 35) = 0.334 with the coefficient of determination = 0.81 or 81%. So limb muscle power m reflected on the contribution to the results of the long jump at the students of SMPN 17 Masaloka Kingdom Bombana.              Based on the results of the analysis, it can be concluded The fish that the stronger power muscular limbs students of SMPN 17 Masaloka Kingdom Bombana will all better the long jump results.